2021
DOI: 10.1080/15614263.2021.1938048
|View full text |Cite
|
Sign up to set email alerts
|

Staffing the force: police staff in England and Wales’ experiences of working through a COVID-19 lockdown

Abstract: This online survey (N = 2365) examined the experiences of (non-sworn /non-warranted) staff serving in police forces in England and Wales during the March to July COVID-19 virus lockdown in the UK. Particular attention was paid to staff working from home, those able to partially work from home and those who remained at work in their usual police location. Home working staff were generally less stressed than those remaining partially or totally at their work location. Public interacting staff were particularly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This paper is the third in an interlinked series reporting some early empirical evidence of the impacts on police personnel during the COVID-19 pandemic experienced by police officers and non-warranted police staff in England and Wales. Results for the female officer respondents were reported in Fleming and Brown (2021a) whilst Fleming and Brown 2021b presented a comparison of police support staff who either worked from home or remained on the front-line. This paper focuses on women personnel, that is, police officers and police support staff and incorporates the dimension of home or front-line working.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is the third in an interlinked series reporting some early empirical evidence of the impacts on police personnel during the COVID-19 pandemic experienced by police officers and non-warranted police staff in England and Wales. Results for the female officer respondents were reported in Fleming and Brown (2021a) whilst Fleming and Brown 2021b presented a comparison of police support staff who either worked from home or remained on the front-line. This paper focuses on women personnel, that is, police officers and police support staff and incorporates the dimension of home or front-line working.…”
Section: Introductionmentioning
confidence: 99%
“…However, elements emerging from the studies conducted after the outbreak and already published, lead us to believe that, in spite of hitches and complications, once telework has been experienced, going back is highly unlikely. Surveys and interviews, confirmed by the analysis of gray literature (Williamson, Pearce, et al, 2022), demonstrate the strong preference of civil servants to sustain this workplace practice (Chow et al, 2022;Singh et al, 2021), which gets as far as to influence their intention to stay (Fleming & Brown, 2022). While pre-pandemic studies often reported a priori resistance to telework of superiors, assumed to be the effect of fears of losing sight and control of their subordinates, original insights come from studies based on the experience of forced remoteness.…”
Section: Discussionmentioning
confidence: 99%
“…Uru et al (2022) suggest that the positive relationship between work engagement and organizational identification is stronger in public employees working remotely. Telework also moderates the relationship between potential stressors and well‐being (Fleming & Brown, 2022; Parent‐Lamarche & Boulet, 2021). According to Giauque et al (2022), telework strengthens the positive association between organizational freedom and employee engagement and perceived performance.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…COVID-19 regulations restricted people's liberty and freedom of movement, and police efforts to enforce the regulations elicited different reactions (Fleming & Brown, 2022). This type of restriction of movement is usually resisted by a section of the public.…”
Section: Introductionmentioning
confidence: 99%